KERANGKA PENELITIAN: MENUJU PENYELESAIAN STUDI DAN PENELITIAN KEAMANAN SIBER: RESEARCH FRAMEWORK: TOWARDS COMPLETION OF CYBERSECURITY STUDY AND RESEARCH - Melwin Syafrizal; Wahid MiftahuL Ashari; Mauludil Asri M Cane (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2025)
This article presents a research framework in cybersecurity developed through a narrative literature review and conceptual analysis. The research process involved four phases: (1) a literature search using keywords related to "research framework" and "cybersecurity" in leading scientific databases; (2) a literature analysis to identify common and specific components in the research design; (3) a synthesis of these components into a systematic research framework; and (4) an enrichment of the framework by considering the unique needs of cybersecurity research, such as ethical aspects, technical experiments, and attack simulations. The resulting research is a Cybersecurity Research Design Framework (CRDF), which comprises ten core steps: identifying the research problem, identifying gaps, formulating the problem, establishing objectives, research questions, a theoretical framework and literature review, research methodology, data collection instruments and techniques, data analysis, and explaining the significance of the research. The CRDF's uniqueness compared to typical computer science research frameworks lies in its integration of specific cybersecurity needs, such as validation through simulations, technical experiments, and consideration of privacy and ethical issues. Thus, CRDF offers not only conceptual guidance but also practical instruments that can help graduate students design more systematic, applicable, and high-quality cybersecurity research.